Effective single web–structured electrode for high membrane electrode assembly performance in polymer electrolyte membrane fuel cell - Ji, Yunseong; Kwon, Ohchan; Jeon, Ok Sung; Yim, Sungdae; Jeon, Yukwon; Shul, Yong-gun (Science advances, 2023)
To achieve a sustainable society, CO 2 emissions must be reduced and efficiency of energy systems must be enhanced. The polymer electrolyte membrane fuel cell (PEMFC) has zero CO 2 emissions and high effectiveness for various applications. A well-designed membrane electrolyte assembly (MEA) composed of electrode layers of effective materials and structure can alter the performance and durability of PEMFC. We demonstrate an efficient electrode deposition method through a well-designed carbon single web with a porous 3D web structure that can be commercially adopted. To achieve excellent electrochemical properties, active Pt nanoparticles are controlled by a nanoglue effect on a highly graphitized carbon surface. The developed MEA exhibits a notable maximum power density of 1082 mW/cm 2 at 80°C, H 2 /air, 50% RH, and 1.8 atm; low cathode loading of 0.1 mg Pt /cm 2 ; and catalytic performance decays of only 23.18 and 13.42% under commercial-based durability protocols, respectively, thereby achieving all desirables for commercial applications. High performance MEA in PEMFC through direct electrode fabrication, using a well-designed and durable carbon single web.